2013
DOI: 10.1021/ol403124g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed α-Arylation of Benzylic Phosphine Oxides

Abstract: A novel approach to prepare diarylmethyl phosphine oxides from benzyl phosphine oxides via deprotonative cross-coupling processes (DCCP) is reported. The optimization of the reaction was guided by High-Throughput Experimentation (HTE) techniques. The Pd(OAc)2/Xantphos-based catalyst enabled the reaction between benzyl diphenyl or dicyclohexyl phosphine oxide derivatives and aryl bromides in good to excellent yields (51–91%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
(27 reference statements)
0
42
0
Order By: Relevance
“…There are numerous silane reducing agents for the preparation of phosphanes from phosphanones in the literature, but in most of those cases it is difficult to get the product from the reaction mixture, or to avoid using a solvent, such as benzene. 24,28,29 We tried to find an easy and simple way for the deoxygenation of phosphanones. First triphenylphosphanone (17) was used as a model compound to investigate the reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous silane reducing agents for the preparation of phosphanes from phosphanones in the literature, but in most of those cases it is difficult to get the product from the reaction mixture, or to avoid using a solvent, such as benzene. 24,28,29 We tried to find an easy and simple way for the deoxygenation of phosphanones. First triphenylphosphanone (17) was used as a model compound to investigate the reduction.…”
Section: Resultsmentioning
confidence: 99%
“…There are reported reductions using triethoxysilane, but in all cases Ti compounds and a solvent, for example benzene are used. [24][25][26][27][28][29][30] In this paper we report an easy way to deoxygenate phosphanones using trimethoxy-or triethoxysilanes without a solvent and a catalyst, gaining macrocycles 1, (R,R)-2, (S,S)-3, (S,S)-4 containing a triphenylphosphane unit. Crown ethers 1 and 5 are already known compounds 14 , here we describe a new route for their preparation, which gives better yields.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that different phosphine ligands are required (Figure 1, ligands L1–L5 ) for the diverse substrate classes and bases we have employed. This method has proven successful for the direct C–H arylation of diarylmethanes ( L1 ), [19] benzylic ketimines ( L1 ), [20] benzyl thioethers, [21] benzylic phosphine oxides ( L2 ), [22] methyl sulfoxides and sulfones ( L3 ), [23] amides ( L3 ), [24] benzylic phosphonates ( L4 ), [25] and allyl benzenes ( L5 ). [26] …”
Section: Resultsmentioning
confidence: 99%
“…Suzuki-Miyaura coupling, Direct C-H arylation Kwong and Walsh [24,57,[59][60][61][62] Amidole-phos (L3)…”
Section: Cyanationmentioning
confidence: 99%
“…Good-to-excellent chemoselectivities (>10:1) between the mono-and diarylated products were achieved by careful selection of bases, solvents, and reagent stoichiometry. A preliminary study showed that NPCy o-Toldole-phos (L2c) was active towards the direct α-arylation of benzylic phosphine oxides [62]. Apart from this type of reaction, palladium catalysts ligated with CM-phos (L1a) also promoted decarboxylative arylation of potassium cyanoacetate [63] and monoarylation of ketones [64].…”
Section: Scheme 11 Palladium-catalyzed Sequential C-h Functionalizatimentioning
confidence: 99%